GAMBARAN PERAN KELUARGA DALAM PENCEGAHAN RISIKO STUNTING PADA ANAK DI WILAYAH KERJA PUSKESMAS SUNGAI KAKAP KABUPATEN KUBU RAYA - Lidia Hastuti; Rona Eka Kusuma; Sri Ariyanti (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2022)
Background: More than half of stunted children under five in the world come from Asia, which is 55%. Stunting is one of the nutritional problems in toddlers that has become a global concern in recent years, especially in low and middle-income countries including Indonesia. One of the factors that influence the incidence of stunting is the role of the family. Families play a role in dealing with children with stunting from pregnancy to fulfillment of nutrition after the baby is born. Objective: to identify the description of the role of the family in preventing the risk of stunting in the working area of the Sungai Kakap Public Health Center, Kubu Raya Regency. Methods: This type of research is descriptive quantitative, with a total sample of 153 respondents selected by purposive sampling. The instrument of data collection was using a questionnaire developed by the researcher. Univariate data analysis using frequency distribution. Results: There are four aspects that are measured in the role of the family, namely the provision of nutrition since pregnancy with a good category of 71.9%, nutritional intake in the good category of 68.6%, exclusive breastfeeding with a good category of 83.0%, and parenting in the family with a good category of 70.6%. Conclusion: the role of families in dealing with children with stunting in the working area of ​​the Sungai Kakap Public Health Center is in the good category.